Super high-density olive orchard system affects the main olive crop pests - Landi, Silvia; Cutino, Ilaria; Simoni, Sauro; Simoncini, Stefania; Benvenuti, Claudia; Pennacchio, Fabrizio; Binazzi, Francesco; Guidi, Silvia; Goggioli, Donatella; Tarchi, Franca; Roversi, Pio Federico; Gargani, Elisabetta (Italian Journal of Agronomy, 2024)
The increasing use of the super high-density (SHD) olive orchard system requires a careful assessment of its potential impact on the main olive pests. The purpose of this study is to evaluate the SHD effect on Bactrocera oleae and other harmful phytophagous species by assessing damages caused by each pest. For three years, in three different sites in Tuscany established with Italian selection or Spanish Arbequina cultivars, the SHD management system was compared to an adjacent traditional olive orchard system in which the same soil and phytosanitary management were applied. Samplings of twigs and fruits from spring to fall together with adult monitoring of B. oleae, Prays oleae, and Palpita vitrealis by pheromone traps were used to determine infestation percentages and insects’ population dynamics. Bactrocera oleae, Liothrips oleae, and Euphillura olivina were negatively affected by the SHD olive orchard system, while P. vitrealis and Otiorhynchus cribricollis were favoured by this management. Bactrocera oleae total infestation was reduced to almost 50% in the SHD system. In contrast, Palpita vitrealis showed high infestation levels in more vigorous cultivars. Further studies are required for a complete evaluation of the impact of SHD management on olive pests.